Exploring the perceptions of NPOs about EU development Aid in facilitating services aimed at women empowerment and children's development in Mauritius - Yone Shin, Yen Mee Cheng (Department of Social Development, 2018)
The study explores how the EDF has enhanced the work of NPOs in the field of women empowerment and children's development in Mauritius. In addition to that, the study explores the outcomes and challenges that NPOs experienced regarding the funding. Using a qualitative and exploratory research approach, this study explores the nature and extent of NPO services that were specifically funded by the European Development Fund. There are five research objectives: to explore the nature and extent of services provided by the NPOs that have been specifically funded by the EDF; to examine how the EU has facilitated the service delivery of the NPOs; to find out how women and children have been empowered; to ascertain how the service delivery has improved the lives of the beneficiaries and to determine the nature of the challenges facing these organisations in the post EU funding period. The findings showed interesting features of the EU funding and the present context of post EU funding. In spite of the small sample of 19 NPOs that participated in this exploratory study, NPO participants have provided valuable insights on how the EU funding have facilitated service delivery towards women empowerment and children's development. The findings showed interesting features of the EU funding and the present context of post EU funding. Obviously more research is needed. The main findings of this research motivated some recommendations that are presented in three different sections. First, recommendations for further research has been presented, followed by some recommendations for NPOs in the sector with regards to accessing funding and finally, some recommendations for the Mauritian government. The key assumptions that EU funding accelerated growth in the NPO sector; increased service delivery and enhanced women and children's development has been confirmed. In conclusion, despite of the limited sample of participants that participated in this exploratory study, they have provided valuable insights into how the European Development Aid has facilitated various development programmes that have made a difference in the lives of women and children.